Obraz Polski i Polaków w tekstach autobiograficznych pisarzy obcych XX i XXI wieku - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2015)
This article in a way constitutes the third part of a cycle of essays on the portrayal of Poland and Poles in autobiographical texts written by foreign authors from the 18th century until the present day. It deals with the 20th and 21st centuries and discusses autobiographical material in which Poland and Polish people feature most heavily (e.g., the diaries of Claudel, Gide, and Mann). Then, the article focuses on several problems, i.e. the Jews and the Jewish question in Poland (e.g. diaries written by Kafka, Gide, Raïssa Maritain, Singer, and Oz), the war (e.g. Queneau’s and Gide’s diaries), Poland after World War II (e.g. the autobiographies of Márai and Oz), and Poland as perceived by travelers (e.g. the diaries of Dublin and others). Topics pertaining to the 21st century are only dealt with here to a limited extent.